O-004 Changes in gene expression of CXCL9 in intracranial distal blood during emergent large vessel occlusion in human stroke. (22nd July 2019) - Fraser, J; Martha, S; Collier, L; Davis, S; Alhajeri, A; Grupke, S; Pennypacker, K
Abstract : Background and purpose: Mechanical thrombectomy (MT) is the standard of care for emergent large vessel occlusion (ELVO), one of the most severe subtypes of ischemic stroke, which accounts for 30–40% of all cases. Through MT, we can isolate distal blood within the artery immediately downstream from the clot and compare it to systemic arterial blood to provide insight into local intraluminal changes during ischemia. CXCL9 is in interferon gamma-inducible chemokine that binds CXCR3, degrading endothelial tight junctions, attracting T cells, and facilitating immune cell extravasation into brain parenchyma. We aimed to study local CXCL9 expression distal to the intracranial thrombus during large vessel occlusion in human patients. Methods: Tissue samples of distal and proximal blood were collected as part of the BACTRAC tissue bank (www.clinicaltrials.gov NCT03153683 ). Adult subjects with ELVO were prospectively enrolled, and arterial blood distal (intracranial) and proximal (cervical) were collected and processed to optimize RNA quality. RNA were isolated and used to evaluate gene expression in both samples for each subject; proximal systemic blood was used as an internal control for each subject. Results: 22 subjects were included in this preliminary analysis. 15 (68.2%) were female. 54.5% of subjects had a CTA collateral score of 1 (18.2% had a score of 0). 4.5% (1 subject) did not attain TICI 2B or 3 recanalization. Infarct time (last known normal to thrombectomy recanalization) was 491 ± 243 minutes. Mean change in NIHSS from admission to discharge was -8 ± 8. CXCL9 expression in distal blood was upregulated an average of 106-fold with a maximum upregulation of 805-fold in one subject. In plotting CXCL9 expression against infarct time, there was a clear negative correlation (Spearman coefficient -0.43, p=0.05). Conclusion: For the first time, we evaluate chemokine alterations in human stroke patients in distal stagnant blood during ELVO. There is a significant variance in CXCL9 expression in distal blood in relationship to infarct time, which mirrors the known timing of blood-brain barrier disruption. Disclosures: J. Fraser: None. S. Martha: None. L. Collier: None. S. Davis: None. A. Alhajeri: None. S. Grupke: None. K. Pennypacker: None.